Computational modeling of air-fuel mixer for natural gas powered motorcycle - 184269 Yeap, Beng Hi (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Master of Engineering (Gas)) - Universiti Teknologi Malaysia, 2002